Health literacy and patient outcomes in chronic kidney disease: a systematic review. Issue 9 (20th November 2017) - Taylor, Dominic M; Fraser, Simon; Dudley, Chris; Oniscu, Gabriel C; Tomson, Charles; Ravanan, Rommel; Roderick, Paul; ,
Abstract: Background: Limited health literacy affects 25% of people with chronic kidney disease (CKD), and may reduce self-management skills resulting in poorer clinical outcomes. By disproportionately affecting people with low socio-economic status and non-white ethnicity, limited health literacy may promote health inequity. Methods: We performed a systematic review of quantitative studies of health literacy and clinical outcomes among adults with CKD. Results: A total of 29 studies (13 articles; 16 conference abstracts) were included. One included non-USA patients. Of the 29 studies, 5 were cohort studies and 24 were cross-sectional. In all, 18 300 patients were studied: 4367 non-dialysis CKD; 13 202 dialysis; 390 transplant; 341 unspecified. Median study size was 127 [interquartile range (IQR) 92–238)], but 480 (IQR 260–2392) for cohort studies. Median proportion of non-white participants was 48% (IQR 17–70%). Six health literacy measures were used. Outcomes included patient attributes, care processes, clinical/laboratory parameters and 'hard' clinical outcomes. Limited health literacy was significantly, independently associated with hospitalizations, emergency department use, missed dialysis sessions, cardiovascular events and mortality (in cohort studies). Study quality was high (1 study), moderate (3 studies) and poor (25 studies), limited by sampling methods, variable adjustment for confounders and reduced methodological detail given in conference abstracts. Conclusions: There is limited robust evidence of the causal effects of health literacy on patient outcomes in CKD. Available evidence suggests associations with adverse clinical events, increased healthcare use and mortality. Prospective studies are required to determine the causal effects of health literacy on outcomes in CKD patients, and examine the relationships between socio-economic status, comorbidity, health literacy and CKD outcomes. Intervention development and evaluation will determine whether health literacy is a modifiable determinant of poor outcomes in CKD.